Technical Efficiency Versus Land-Use Efficiency: A Spatio-Temporal Efficiency Analysis of China's Crop Production - Fang Yin; Zhanli Sun; Liangzhi You; Vivian Wei Huang (German Journal of Agricultural Economics (GJAE), 2024)
Improved land-use efficiency in agricultural production is crucial to meet increasing demand for agricultural commodities using the finite area of arable land worldwide. By applying a spatial autoregressive stochastic frontier methodology to county-level data spanning from 1980 to 2011, we conducted an analysis to investigate changes in both the spatial and temporal dimensions of technical efficiency and land-use efficiency within Chinese crop production. During this period, China achieved a remarkable upsurge in food production, notably within the first three decades of the rural reform that began in 1978. There were substantial transformations in agricultural land use that encompassed changes in cropland areas, shifts in the composition of various crops, alterations in their geographical distributions and enhancements in crop yields. Based on the results of this analysis, land-use efficiency increased slightly from 0.47 to 0.56 in most regions of China during that period and became convergent over time, with spatial gaps narrowing. National technical efficiency increased by 20 % on average, but with substantial regional variations, e.g. lower technical efficiency gains in northeast and northwest China and greater technical efficiency in the north and south. Urbanisation was found to be positively associated with lower technical efficiency, while a greater distance from provincial capitals resulted in higher technical efficiency. Efficient land use can lead to greater agricultural productivity, which, in turn, can boost rural economies and contribute to overall economic growth. These results could help in the design of effective regional policies to optimise land-use efficiency in crop production.
Keywords: 330; Spatial Spillover; Spatial Autoregressive Model; Stochastic Frontier Analysis; Production Function